PENGARUH SQUARE STEPPING EXERCISE DAN ANKLE STRATEGY EXERCISE TERHADAP KESEIMBANGAN PADA LANSIA - Sabri, Aiman; Sulaiman, Sulaiman; Maryaningsih, Maryaningsih (Prodi Fisioterapi UFDK, 2023)
The health status of the elderly which declines with age will affect the quality of life of the elderly. Increasing age will be accompanied by the emergence of various diseases, decreased body function, body balance and the risk of falling. Research objectives: To analyze whether there is an effect of giving Square Stepping Exercise and Ankle Strategy Exercise to changes in the level of dynamic balance of the elderly. Research method: The design of this study is Quasi Experimental using